Evaluasi Layanan E-Channel Samsat dalam Pembayaran Pajak Kendaraan Bermotor di Kantor Bersama Samsat Sampang - Mahbuby, Wildan; Sunarya, Aris (Soetomo Magister Ilmu Administrasi, 2025)
This research was conducted to determine the evaluation of E-channel services for special tax vehicles in Sampang district by evaluating services and supporting factors as well as inhibiting factors in the E-channel program. This research uses the Evaluation Method with data collection techniques in the form of interviews and documentation. The object of the research is at the Joint Samsat Sampang, Indomaret, Samsat Sampang and Motor Vehicle Taxpayers offices in Sampang. The research results show that it has not shown significant benefits, so it has proven to be less effective in terms of administration. Supporting factors in this E-channel include, in terms of faster time than conventional tax payments, easier payment methods with the PPOB (payment point of bank) system and working with various bank options, and Indomart. The main inhibiting factors found were that E-channel was not fully online, there was a lack of socialization of E-channel to the public, and the habit of using related services was still carried out by the majority of Sampang district residents. Internet and connection problems are also obstacles in using E-channel. As a recommendation to achieve better E-channel goals, it is hoped that the Regional Revenue Service can collaborate with the police regarding E-channel becoming a full online system. The government and BPD of East Java can intensify direct outreach to communities such as universities and every village.